+0  
 
0
181
1
avatar

t_1 (first term): p^2/2

 

r (common ratio): p/2

 

t_n (nth term): p^9/256

Guest Nov 6, 2017
 #1
avatar+87635 
+1

We need to solve this :

 

(p^2 / 2 ) * (p/2)^(n -1)  = p^9 / 256    where n is the nth term

 

Multiply through by  2 / p^2

 

(p / 2)^(n -1)  =  p^7 / 128

 

Note   p^7 / 128  =   p^7 / 2^7  =  ( p / 2)^7

 

So......

 

(p / 2) ^(n - 1)  =  (p /2 )^7

 

Since the bases are the same, solve for the exponents

 

n - 1  = 7      add 1 to both sides

 

n  =  8   terms

 

 

cool cool cool

CPhill  Nov 6, 2017

5 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.